Silicon-based negative electrode containing nitrogen modification layer, preparation method of silicon-based negative electrode and lithium ion battery
By coating the surface of silicon-based particles with nitrogen modification layer, a SEI film containing Li3N is generated, which solves the problem of battery instability caused by volume effect of silicon-based materials and improves the performance and stability of lithium-ion batteries.
Patent Information
- Application Number
- CN202510399423.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-07-04
AI Technical Summary
The silicon-based materials are high internal stress and unstable SEI interface in lithium-ion batteries due to volume effects, which affect the battery's rate performance, low-temperature capacity retention rate and cycle stability.
The surface of silicon-based particles is coated with a nitrogen-modified layer, and the nitrogen-containing organic matter and oxygen elements are connected through chemical bonds to form a SEI film containing Li3N, buffering volume changes and promoting Li+ diffusion.
The rate performance, low-temperature capacity retention and cycle stability of lithium-ion batteries are improved, and the active material is protected by flexible and mechanical stability SEI films.
Smart Images

Figure CN120261487A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium-ion batteries, and particularly to a silicon-based negative electrode with a nitrogen-modified layer, a preparation method thereof, and a lithium-ion battery. Background Art
[0002] With the continuous progress of new energy technologies, lithium-ion batteries, as energy storage devices with high energy density and low cost, have become a hot topic in modern industrial and scientific research fields. Facing the challenges that lithium-ion batteries may encounter in practical applications, rapid charging and excellent low-temperature tolerance of the batteries become particularly crucial. These performances not only ensure the rapid charge and discharge characteristics and the maintenance of high energy density of the batteries in harsh environments, but also guarantee the stability and reliability of the devices at critical moments.
[0003] In lithium-ion batteries, compared with traditional graphite negative electrode materials, silicon-based materials have higher theoretical specific capacity and lower lithium deintercalation potential, and can avoid the phenomenon of lithium deposition on the surface during charging. However, the severe volume effect during lithiation is the biggest limitation for the commercialization of silicon-based materials: the volume effect will cause large internal stress in the battery, easily squeeze the electrode sheet, resulting in cracks and even pulverization of the silicon negative electrode material; in addition, the volume expansion effect is prone to form an unstable SEI interfacial film. Since the SEI will break as the silicon volume changes, the newly exposed silicon on the surface will produce a new SEI film, and at the same time, it will continuously consume lithium ions in the electrolyte, leading to irreversible capacity loss and low initial Coulomb efficiency. Moreover, the SEI thickness will increase continuously with the electrochemical cycle, and the generated overly thick SEI layer will hinder electron transfer and Li + ion diffusion, resulting in an increase in impedance, seriously affecting the rate performance, low-temperature capacity retention rate, and cycle stability of the battery. Summary of the Invention
[0004] The present invention provides a silicon-based negative electrode with a nitrogen-modified layer, a preparation method thereof, and a lithium-ion battery. The silicon-based negative electrode of the present invention improves the rate performance, low-temperature capacity retention rate, and cycle stability of the lithium-ion battery.
[0005] The present invention provides a silicon-based negative electrode with a nitrogen-modified layer, including silicon-based particles with oxygen element on the surface and a nitrogen-modified layer coated on the surface of the silicon-based particles; the nitrogen element and the oxygen element in the nitrogen-modified layer are connected by chemical bonds;
[0006] The compound in the nitrogen-modified layer is a nitrogen-containing organic compound;
[0007] The nitrogen-containing organic compound is one or more of alkylamine, amide compounds containing two or more amino groups, thioamide compounds, nitrogen heterocyclic compounds, nitrile compounds, and nitro compounds.
[0008] Preferably, the silicon-based particles include pure silicon, silicon oxide, silicon-carbon composite, graphite-silicon oxide composite, One or more of graphite, silicon-carbon composite, and metal-coated silicon material.
[0009] Preferably, the nitro compound includes nitrobenzyl alcohol and / or nitroethane.
[0010] Preferably, the thickness of the nitrogen-modified layer is 1 to 50 nm.
[0011] The present invention also provides a method for preparing the silicon-based negative electrode described in the above technical solution, including the following steps:
[0012] Oxidize the silicon-based particles to generate oxygen-containing functional groups on the surface to obtain oxidized silicon-based particles;
[0013] Mix the oxidized silicon-based particles with a nitrogen-containing organic compound and then perform heat treatment to obtain the silicon-based negative electrode;
[0014] The heat treatment is carried out in a protective atmosphere.
[0015] Preferably, the mass ratio of the oxidized silicon-based particles to the nitrogen-containing organic compound is 1:0.1 to 10.
[0016] Preferably, when the nitrogen-containing organic compound is a solid, the raw materials for mixing further include: a solvent or a solvent and a surfactant.
[0017] Preferably, the heat treatment includes a first heat treatment and a second heat treatment;
[0018] The temperature of the first heat treatment is 45 to 80 °C;
[0019] The temperature of the second heat treatment is 120 to 350 °C, and the time is 2 to 6 h.
[0020] The present invention also provides a lithium-ion battery, including a silicon-based negative electrode, a positive electrode, a separator, and an electrolyte; the silicon-based negative electrode is the silicon-based negative electrode described in the above technical solution or the silicon-based negative electrode prepared by the preparation method described in the above technical solution.
[0021] The present invention also provides a lithium-ion battery, including a silicon-based negative electrode coated with an SEI film, a positive electrode, a separator, and an electrolyte; the silicon-based negative electrode coated with an SEI film is formed by the silicon-based negative electrode described in the above technical solution or the silicon-based negative electrode prepared by the preparation method described in the above technical solution during charge and discharge with the electrolyte; the SEI film contains Li3N; the thickness of the SEI film is 1 to 50 nm.
[0022] The nitrogen-modified layer containing the nitrogen-containing organic compounds of the present invention can induce the reaction between the silicon-based anode and the electrolyte at the initial stage of battery charge and discharge to generate a SEI film containing Li3N. The inorganic component Li3N in the SEI film can prevent the continuous decomposition of the electrolyte on the silicon surface, and has relatively high flexibility and mechanical stability, which can effectively repair the damaged surface microstructure and regulate the Li + diffusion path, thereby reactivating the stability of the interfacial film. Inorganic Li3N has extremely high ionic conductivity (≈10 -3 S cm -1 ), Young's modulus and thermodynamic stability, and can also promote the diffusion of Li + ions at the interface. Therefore, the formation of a SEI interfacial film rich in Li3N on the silicon-based anode can help buffer the huge volume change of the silicon-based anode during charge and discharge, protect the active material, and enable the silicon-based anode with a Li3N-rich interface to have more prominent rate performance, low-temperature capacity retention rate, and long cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the structure of the silicon-based anode material with a Li3N-containing SEI film;
[0024] Figure 2 Fourier transform infrared spectrum of the oxidized nano-silicon oxide particles in Example 1 of the present invention;
[0025] Figure 3 Low-temperature charge and discharge curves of the lithium-ion batteries in Example 1 and Comparative Example 1;
[0026] Figure 4 Long cycle performance graph of the lithium-ion battery in Example 1. DETAILED DESCRIPTION OF THE INVENTION
[0027] The present invention provides a silicon-based anode with a nitrogen-modified layer, which includes silicon-based particles with oxygen on the surface and a nitrogen-modified layer coated on the surface of the silicon-based particles; the nitrogen element and the oxygen element in the nitrogen-modified layer are connected by chemical bonds;
[0028] The compound in the nitrogen-modified layer is a nitrogen-containing organic compound;
[0029] The nitrogen-containing organic compound is one or more of alkylamine, amide compounds containing two or more amino groups, thioamide compounds, nitrogen heterocyclic compounds, nitrile compounds, and nitro compounds.
[0030] The silicon-based anode with a nitrogen-modified layer provided by the present invention includes silicon-based particles with oxygen on the surface. The silicon-based particles preferably include one or more of pure silicon, silicon oxide, silicon-carbon composite, graphite and silicon oxide composite, graphite and silicon-carbon composite, and metal-coated silicon material.
[0031] The silicon-based anode with a nitrogen-modified layer provided by the present invention comprises a nitrogen-modified layer coated on the surface of the silicon-based particles; the thickness of the nitrogen-modified layer is preferably 1 to 50 nm. In specific embodiments of the present invention, the thickness of the nitrogen-modified layer can be 1 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm or 50 nm. The compound in the nitrogen-modified layer is a nitrogen-containing organic compound; the nitrogen-containing organic compound is one or more of alkyl amines, amide compounds containing two or more amino groups, thioamide compounds, nitrogen heterocyclic compounds, nitrile compounds and nitro compounds; the nitro compound preferably includes nitrobenzyl alcohol and / or nitroethane; the amide compound containing two or more amino groups preferably includes urea; the thioamide compound preferably includes thiourea; the alkyl amine preferably includes aniline and / or triethylamine.
[0032] The present invention also provides a method for preparing the silicon-based anode according to the above technical solution, comprising the following steps:
[0033] Performing an oxidation treatment on the silicon-based particles to generate oxygen-containing functional groups on the surface, thereby obtaining oxidized silicon-based particles;
[0034] Mixing the oxidized silicon-based particles, the nitrogen-containing organic compound and a solvent, followed by drying and heat treatment to obtain the silicon-based anode;
[0035] The heat treatment is carried out in a protective atmosphere.
[0036] In the present invention, an oxidation treatment is performed on the silicon-based particles to generate oxygen-containing functional groups on the surface, thereby obtaining oxidized silicon-based particles.
[0037] In the present invention, the oxidation treatment preferably includes: mixing the silicon-based particles with an oxygen-containing oxidant Performing an oxidation reaction.
[0038] In the present invention, the oxygen-containing oxidant preferably includes one or more of oxygen, air, oxygen-containing acids and hydrogen peroxide.
[0039] After obtaining the oxidized silicon-based particles, in the present invention, the oxidized silicon-based particles are mixed with a nitrogen-containing organic compound and then subjected to heat treatment to obtain the silicon-based anode.
[0040] In the present invention, when the nitrogen-containing organic compound is a solid, the raw materials for mixing further include: a solvent or a solvent and a surfactant;
[0041] When the raw materials for mixing include a solvent and a surfactant, the mixing preferably includes: dissolving the nitrogen-containing organic compound in the solvent, and then mixing the obtained solution with the oxidized silicon-based particles.
[0042] When the raw materials for mixing include a solvent, the mixing preferably includes: dissolving the nitrogen-containing organic compound in the solvent, then mixing the obtained solution with the oxidized silicon-based particles, and then mixing the obtained mixture with the surfactant.
[0043] In the present invention, the solvent preferably includes ethanol and / or water.
[0044] In the present invention, the mass ratio of the silicon oxide-based particles to the nitrogen-containing organic compound is preferably 1:0.1 to 10. In specific embodiments of the present invention, the mass ratio of the silicon oxide-based particles to the nitrogen-containing organic compound can be 1:0.1, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, or 1:10.
[0045] The present invention controls the thickness of the nitrogen-containing modification layer by controlling the type and amount of the nitrogen-containing organic compound, and further controls the thickness of the generated SEI.
[0046] In the present invention, the mass of the surfactant is preferably 20 to 30% of the mass of the nitrogen-containing organic compound. In specific embodiments of the present invention, the mass of the surfactant can be 20%, 22%, 24%, 26%, 28%, or 30% of the mass of the nitrogen-containing organic compound; the surfactant preferably includes sodium dodecyl sulfonate.
[0047] In the present invention, the heat treatment preferably includes a first heat treatment and a second heat treatment; the temperature of the first heat treatment is preferably 45 to 80°C. In specific embodiments of the present invention, the temperature of the first heat treatment can be 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, or 80°C; when the temperature of the second heat treatment is 150 to 350°C, the time of the first heat treatment is preferably 4 to 6 h. In specific embodiments of the present invention, the time can be 4 h, 5 h, or 6 h; when the temperature of the second heat treatment is 120 to 150°C and not 150°C, there is no special limitation on the time of the first heat treatment in the present invention, and it is only necessary to remove the solvent.
[0048] In the present invention, the first heat treatment is preferably carried out in a protective atmosphere or under air conditions. When the the nitrogen-containing When the organic matter and the solvent are dangerous in air at the temperature of the first heat treatment, the first heat treatment is carried out in a protective atmosphere. For example, when the nitrogen-containing organic compound is triethylamine, triethylamine may explode when it enters the air.
[0049] In the present invention, when the solvent will introduce impurities, preferably further included after the first heat treatment and before the second heat treatment is: washing and drying the product obtained from the first heat treatment. In specific embodiments of the present invention, when the solvent is dimethyl sulfoxide, the product obtained from the first heat treatment is washed and dried.
[0050] In the present invention, the second heat treatment is carried out in a protective atmosphere, and the gas in the protective atmosphere preferably includes argon and / or nitrogen.
[0051] The temperature of the second heat treatment is preferably 120 to 350 °C, and the time is preferably 2 to 6 h. In a specific embodiment of the present invention, the temperature of the second heat treatment can be 120 °C, 150 °C, 180 °C, 200 °C, 240 °C, 250 °C, 280 °C, 300 °C or 350 °C, and the time can be 2 h, 3 h, 4 h, 5 h or 6 h.
[0052] During the heat treatment, covalent bonds are formed between the oxygen-containing functional groups on the surface of the silica-based particles and the nitrogen atoms in the nitrogen-containing organic matter, so that the nitrogen-containing organic matter forms a coating on the silica-based particles.
[0053] After the heat treatment, the present invention preferably washes and dries the product obtained by the heat treatment.
[0054] The present invention also provides a lithium-ion battery, including a silicon-based negative electrode, a positive electrode, a separator and an electrolyte; the silicon-based negative electrode is the silicon-based negative electrode described in the above technical solution or the silicon-based negative electrode prepared by the preparation method described in the technical solution.
[0055] The present invention also provides a lithium-ion battery, including a silicon-based negative electrode coated with an SEI film, a positive electrode, a separator and an electrolyte; the silicon-based negative electrode coated with the SEI film is formed during the charge and discharge process with the electrolyte of the silicon-based negative electrode described in the above technical solution or the silicon-based negative electrode prepared by the preparation method described in the above technical solution; the SEI film contains Li3N; the thickness of the SEI film is 1 to 50 nm.
[0056] If the thickness of the SEI film is too low, an insufficient Li3N protective layer cannot be formed, and if the thickness is too large, the Li + transmission in the interface becomes slower.
[0057] Figure 1 It is a schematic structural diagram of a silicon-based negative electrode material with an SEI film containing Li3N.
[0058] The following combines examples to detail the nitrogen-modified layer-containing silicon-based negative electrode provided by the present invention, its preparation method, and the lithium-ion battery, but they cannot be understood as limiting the protection scope of the present invention.
[0059] Example 1
[0060] Disperse 1.5 g of nano-silica particles in 50 mL of ethanol, then add 30 mL of a hydrogen peroxide solution with a mass concentration of 30% and react at 45 °C for 3 h to perform surface hydroxylation treatment on the silica particles. Subsequently, wash with deionized water multiple times and dry to obtain oxidized nano-silica particles.
[0061] Figure 2 Fourier transform infrared spectrum of the oxidized nano-silicon oxide particles of Embodiment 1 of the present invention.
[0062] From Figure 2It can be seen that oxygen-containing functional groups (-O-H) appear on the surface of the silicon oxide particles after oxidation treatment, providing reaction sites for the subsequent chemical bond connection between the nitrogen source and the oxygen atoms in the oxygen-containing functional groups.
[0063] Disperse 1.5 g of the prepared oxidized nano-silicon oxide particles in 4 g of aniline (PhNH2). Then, add 1.0 g of sodium dodecyl sulfate (SDS) to the mixed sample and perform ultra-high speed emulsification at a rotation speed of 12000 r / min for 10 min. Subsequently, put the obtained emulsion into a three-necked flask, perform heat treatment at 80 °C for 4 h, and then perform heat treatment at 300 °C for 4 h under the protection of a nitrogen atmosphere. After taking out the product, wash it with deionized water and ethanol (to remove residual reagents) and dry it overnight to obtain SiO x @PhNH2.
[0064] Under anhydrous and anaerobic conditions, dissolve lithium hexafluorophosphate (LiPF6) as a lithium salt into a mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) (v (EC) :v (DMC) = 3:7) to obtain an electrolyte solution (COE) with a LiPF6 concentration of 1 mol / L.
[0065] Using COE as the electrolyte, SiO modified by the above method x (SiO x @PhNH2) is used to prepare a positive electrode material (the preparation method of the positive electrode material is as follows: uniformly mix SiO x @PhNH2 powder (0.8 g), polyacrylic acid binder (PAA) and SuperP conductive agent in a mass ratio of 8:1:1 to prepare a slurry. Subsequently, uniformly coat the slurry on a copper foil to form a pole piece coating. After coating, place the pole piece in a vacuum drying oven at 80 °C and perform baking treatment for 12 h to ensure that the slurry is fully dried), lithium metal (Li) as the negative electrode material, and polypropylene (PP, Celgard 2500) as the separator to assemble a coin-type half cell. Charge and discharge at a rate of 0.1C, the capacity at room temperature of 25 °C is 1215 mAh / g, and the capacity at low temperature of -20 °C is 982 mAh / g; the charge and discharge capacity at a rate of 8C at room temperature is 854 mAh / g, and the capacity retention rate after 200 cycles at a rate of 0.2C is 77%.
[0066] Figure 3 It is the low-temperature charge and discharge curves of the lithium-ion batteries in Example 1 and Comparative Example 1.
[0067] Figure 4 It is the long cycle performance graph of the lithium-ion battery in Example 1.
[0068] Example 2
[0069] Dissolve 1 g of 3-nitrobenzyl alcohol (NOBA, C7H7NO3) in 99 g of ethanol to prepare a 1 wt% NOBA solution.
[0070] Then, 1 g of the oxidized nano-silicon oxide particles of Example 1 was dispersed into 10 mL of the 1 wt% NOBA solution under high-speed stirring. While vigorously stirring, the suspension was heated to 70 °C in a water bath until the mixture was completely dried. To establish a chemical bridge through the dehydration between NOBA and the -OH groups on the Si surface, the obtained sample was further heated at 120 °C under vacuum conditions (nitrogen environment, 10 Pa) for 6 h. After taking out the product, it was washed with deionized water and ethanol (to remove residual reagents) and dried overnight to obtain SiO x @NOBA.
[0071] Using COE as the electrolyte, the SiO x (SiO x @NOBA) was used to prepare the positive electrode material (The positive electrode material The preparation method is as follows: SiO x @NOBA powder (0.8 g), polyacrylic acid binder (PAA) and SuperP conductive agent were uniformly mixed in a mass ratio of 8:1:1 to prepare a slurry. Subsequently, the slurry was uniformly coated on a copper foil to form a pole piece coating. After coating, the pole piece was placed in a vacuum drying oven at 80 °C for 12 h of baking treatment to ensure that the slurry was fully dried), lithium metal (Li) was used as the negative electrode material, and polypropylene (PP, Celgard 2500) was used as the separator to assemble a button-type half-cell. Charging and discharging were carried out at a rate of 0.1C. The capacity at room temperature of 25 °C was 1216 mAh / g, and the capacity at low temperature of -20 °C was 985 mAh / g; the charging and discharging capacity at a rate of 8C at room temperature was 879 mAh / g, and the capacity retention rate after 200 cycles at a rate of 0.2C was 81%.
[0072] Example 3
[0073] Dissolve 2 g of nitroethane (C2H5NO2) in 98 g of ethanol to prepare a nitroethane solution.
[0074] In a glove box, 1 g of the oxidized nano-silicon oxide particles of Example 1 was added to 10 mL of the above nitroethane solution, stirred until evenly dispersed, and reacted at 80 °C for 4 h. Subsequently, the mixture was sealed, heated to 300 °C in a nitrogen atmosphere, and maintained for 2 h. After taking out the product, it was washed with deionized water and ethanol (to remove residual reagents) and dried overnight to obtain SiO x @C2H5NO2 material.
[0075] Using COE as the electrolyte, the SiO x (SiO x @C2H5NO2) was used to prepare the positive electrode material (the preparation method of the positive electrode material is: SiOx The @C2H5NO2 powder (0.8 g), polyacrylic acid binder (PAA), and SuperP conductive agent were uniformly mixed in a mass ratio of 8:1:1 to prepare a slurry. Subsequently, the slurry was uniformly coated on a copper foil to form a cathode coating. After coating, the cathode was placed in a vacuum drying oven at 80 °C for 12 h of baking treatment to ensure that the slurry was fully dried. Lithium metal (Li) was used as the anode material, and polypropylene (PP, Celgard 2500) was used as the separator to assemble a coin-type half-cell. Charging and discharging were carried out at a rate of 0.1C. The capacity at room temperature of 25 °C was 1201 mAh / g, and the capacity at low temperature of -20 °C was 970 mAh / g; the charging and discharging capacity at a rate of 8C at room temperature was 832 mAh / g, and the capacity retention rate after 200 cycles at a rate of 0.2C was 82%.
[0076] Example 4
[0077] 4 g of triethylamine (TEA) was dissolved in 96 g of ethanol to prepare a triethylamine solution.
[0078] 1.5 g of the oxidized nano-silicon oxide particles of Example 1 were dispersed in 100 g of the triethylamine solution and stirred thoroughly. Subsequently, the reaction was carried out at a temperature of 45 °C for 6 h in a nitrogen atmosphere. The reaction product was heat-treated in a nitrogen atmosphere at a temperature of 240 °C for 4 h. After the product was taken out, it was washed with deionized water and ethanol (to remove residual reagents) and dried overnight to obtain the final SiO x @TEA.
[0079] Using COE as the electrolyte, the SiO modified by the above method x (SiO x @TEA) was used to prepare the cathode material (the preparation method of the cathode material was as follows: the SiO x @TEA powder (0.8 g), polyacrylic acid binder (PAA), and SuperP conductive agent were uniformly mixed in a mass ratio of 8:1:1 to prepare a slurry. Subsequently, the slurry is uniformly coated on the copper foil to form a pole piece coating. After the coating is completed, the pole piece is placed in a vacuum drying was placed in a drying oven for 12 h of baking treatment to ensure that the slurry was fully dried. Lithium metal (Li) was used as the anode material, and a coin-type half-cell was assembled. Charging and discharging were carried out at a rate of 0.1C. The capacity at room temperature of 25 °C was 1210 mAh / g, and the capacity at low temperature of -20 °C was 968 mAh / g; the charging and discharging capacity at a rate of 8C at room temperature was 801 mAh / g, and the capacity retention rate after 200 cycles at a rate of 0.2C was 76%.
[0080] Example 5
[0081] Urea (CH4N2O) was dissolved in dimethyl sulfoxide (DMSO) solvent to form a 5 wt% urea solution.
[0082] 1.5 g of the oxidized nano-silicon oxide particles of Example 1 were dispersed in 50 mL of the above solution. The mixed solution was placed in a three-necked flask and stirred at 80 °C for 4 h. After the reaction was completed, the product was filtered and washed with ethanol. After drying, the mixture was sealed, heated to 350 °C in an argon atmosphere, and maintained for 3 h. After the product was taken out, it was washed with deionized water and ethanol (to remove residual reagents) and dried overnight to obtain SiO x @CH4N2O material.
[0083] Using COE as the electrolyte, the SiO modified by the above method x (SiO x @CH4N2O) was used to prepare the positive electrode material (the preparation method of the positive electrode material is as follows: SiO x @CH4N2O powder (0.8 g), polyacrylic acid binder (PAA), and SuperP conductive agent were uniformly mixed according to a mass ratio of 8:1:1 to prepare a slurry. Subsequently, the slurry was uniformly coated on a copper foil to form a pole piece coating. After coating, the pole piece was placed in a vacuum drying oven at 80 °C for 12 h of baking treatment to ensure that the slurry was fully dried), lithium metal (Li) was used as the negative electrode material, and polypropylene (PP, Celgard 2500) was used as the separator to assemble a coin-type half-cell. Charging and discharging were carried out at a rate of 0.1C. The capacity at room temperature of 25 °C was 1198 mAh / g, and the capacity at low temperature of -20 °C was 947 mAh / g; the charging and discharging capacity at a rate of 8C at room temperature was 789 mAh / g, and the capacity retention rate after 200 cycles at a rate of 0.2C was 77%.
[0084] Example 6
[0085] Thiourea (CH4N2S) was dissolved in deionized water to form a 5 wt% thiourea solution.
[0086] 2 g of the oxidized nano-silicon oxide particles of Example 1 were added to 50 mL of the thiourea solution. After stirring evenly, the temperature was set to 60 °C and the reaction was carried out for 6 h. Subsequently, the mixture was placed in a tubular furnace, and argon was passed as a protective gas, and the reaction was carried out at 350 °C for 2 h. After the reaction was completed, the product was taken out, washed with deionized water and ethanol (to remove residual reagents) and dried overnight to obtain SiO x @CH4N2S.
[0087] Using COE as the electrolyte, the SiO modified by the above method x (SiO x @CH4N2S) was used to prepare the positive electrode material (the preparation method of the positive electrode material is as follows: SiO x@CH4N2S powder (0.8 g), polyacrylic acid binder (PAA), and SuperP conductive agent were uniformly mixed at a mass ratio of 8:1:1 to prepare a slurry. Subsequently, the slurry was uniformly coated on a copper foil to form a pole piece coating. After coating, the pole piece was placed in a vacuum at 80 °C oven at 80 °C and baked for 12 h to ensure that the slurry is fully dried), Lithium metal (Li) is used as the negative electrode material material, polypropylene (PP, Celgard 2500) as the separator, and a coin-type half-cell was assembled. Charge and discharge were carried out at a rate of 0.1C. The capacity at room temperature of 25 °C was 1215 mAh / g, and the capacity at low temperature of -20 °C was 960 mAh / g; the charge and discharge capacity at a rate of 8C at room temperature was 821 mAh / g, and the capacity retention rate after 200 cycles at a rate of 0.2C was 86%.
[0088] Comparative Example 1
[0089] Using the oxidized nano-silicon oxy particles (SiO x ) of Example 1 to prepare a positive electrode material (the preparation method of the positive electrode material is: 0.8 g of SiO x powder, polyacrylic acid binder (PAA), and SuperP conductive agent were uniformly mixed at a mass ratio of 8:1:1 to prepare a slurry. Subsequently, the slurry was uniformly coated on a copper foil to form a pole piece coating. After coating, the pole piece was placed in a vacuum drying oven at 80 °C and baked for 12 h to ensure that the slurry was fully dried), lithium metal (Li) as the negative electrode material, COE as the electrolyte, polypropylene (PP, Celgard 2500) as the separator, and a coin-type half-cell was assembled. Charge and discharge were carried out at a rate of 0.1C. The capacity at room temperature of 25 °C was 972 mAh / g, and the capacity at low temperature of -20 °C was 530 mAh / g; the charge and discharge capacity at a rate of 8C at room temperature was 200 mAh / g, and the capacity retention rate after 200 cycles at a rate of 0.2C was 37%.
[0090] Comparative Example 2
[0091] 1 g of the oxidized nano-silicon oxy particles of Example 1 was added to 100 mL of formamide (HCO-NH2) and stirred well. The reaction system was placed in an environment at 50 °C and reacted for 3 h. Subsequently, the reaction mixture was transferred to a tube furnace and reacted at a temperature of 350 °C for 3 h under an argon protection atmosphere. After the reaction was completed, the product was taken out and washed repeatedly with deionized water and ethanol to remove the residual reagents, and then dried overnight at room temperature to finally obtain SiO x @HCO-NH2.
[0092] Using COE as the electrolyte, the SiO x (SiO x @HCO-NH2) prepared by the above method to prepare a positive electrode material (the preparation method of the positive electrode material is: SiO x@HCO-NH2 powder (0.8 g), polyacrylic acid binder (PAA), and SuperP conductive agent were uniformly mixed in a mass ratio of 8:1:1 to prepare a slurry. Subsequently, the slurry was uniformly coated on a copper foil to form a cathode coating. After coating, the cathode was placed in a vacuum drying oven at 80 °C for 12 h of baking treatment to ensure that the slurry was fully dried. Lithium metal (Li) was used as the anode material, and polypropylene (PP, Celgard 2500) was used as the separator to assemble a coin-type half-cell. Charging and discharging were carried out at a rate of 0.1C. The capacity at room temperature of 25 °C was 615 mAh / g, and the capacity at low temperature of -20 °C was 160 mAh / g; the capacity at a rate of 8C at room temperature was 91 mAh / g, and the capacity retention rate after 200 cycles at 0.2C was 16%.
[0093] Table 1 shows the battery capacities and capacity retention rates under different conditions in Examples 1-6 and Comparative Examples 1-2.
[0094] Table 1 Battery capacities and capacity retention rates under different conditions in Examples 1-6 and Comparative Examples 1-2
[0095]
[0096] As can be seen from Table 1, as a nitrogen-containing compound, the performance of the coin-type half-cell prepared with formamide is greatly reduced.
[0097] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.
Claims
1. A silicon-based anode with a nitrogen-containing modification layer, characterized in that, It includes silicon-based particles with oxygen-containing elements on the surface and a nitrogen-modified layer coated on the surface of the silicon-based particles; nitrogen elements and oxygen elements in the nitrogen-modified layer are connected by chemical bonds; The compound in the nitrogen-modified layer is a nitrogen-containing organic compound; The nitrogen-containing organic compound is one or more of alkylamine, amide compounds with two or more amino groups, thioamide compounds, nitrogen heterocyclic compounds, nitrile compounds, and nitro compounds.
2. The silicon-based negative electrode according to claim 1, wherein The silicon-based particles include one or more of pure silicon, silicon oxide, silicon-carbon composite, graphite and silicon oxide composite, graphite and silicon-carbon composite, and metal-coated silicon materials.
3. The silicon-based negative electrode according to claim 1, wherein, The nitro compounds include nitrobenzyl alcohol and / or nitroethane; the amide compounds with two or more amino groups include and / or urea; the thioamide compounds include thiourea; the alkylamine includes aniline and / or triethylamine.
4. The silicon-based negative electrode according to claim 1 or 3, characterized in that The thickness of the nitrogen-modified layer is 1-50 nm.
5. The preparation method of the silicon-based negative electrode according to any one of claims 1 to 4, characterized in that, It includes the following steps: Oxidize the silicon-based particles to generate oxygen-containing functional groups on the surface to obtain oxidized silicon-based particles; Mix the oxidized silicon-based particles with a nitrogen-containing organic compound and then perform heat treatment to obtain the silicon-based negative electrode; The heat treatment is carried out in a protective atmosphere.
6. The preparation method according to claim 5, wherein The mass ratio of the oxidized silicon-based particles to the nitrogen-containing organic compound is 1:0.1-10.
7. The preparation method according to claim 6, characterized in that, When the nitrogen-containing organic compound is a solid, the mixed raw materials also include: a solvent or a solvent and a surfactant.
8. The preparation method according to claim 6 or 7, characterized in that, The heat treatment includes a first heat treatment and a second heat treatment; The temperature of the first heat treatment is 45-80 °C; The temperature of the second heat treatment is 120-350 °C, and the time is 2-6 h.
9. A lithium-ion battery, characterized in that, It includes a silicon-based negative electrode, a positive electrode, a separator, and an electrolyte; the silicon-based negative electrode is the silicon-based negative electrode according to any one of claims 1-4 or the silicon-based negative electrode prepared by the preparation method according to any one of claims 5-8.
10. A lithium-ion battery, characterized in that, It includes a silicon-based negative electrode coated with an SEI film, a positive electrode, a separator, and an electrolyte; the silicon-based negative electrode coated with an SEI film is formed during charge and discharge of the silicon-based negative electrode according to claim 4 or the silicon-based negative electrode prepared by the preparation method according to any one of claims 6-8 and the electrolyte. The SEI film contains Li3N; the thickness of the SEI film is 1-50 nm.